ANALYSIS OF ELEMENTARY SCHOOL STUDENTS ABILITY IN MATHEMATICS LITERACY (International Conference on Elementary Education, 2018)
This study is motivated by the importance of mathematics literacy abilities of elementary school students in relation to 21st century education issues. The purpose of this study is to find out how students are able to apply mathematical concepts in problems that arise in everyday life and the factors that influence them. The research design used was descriptive qualitative. This research was carried out on 30 fourth grade elementary school students in Bandung regency by giving mathematics literacy tests and followed by interviews. The results showed that the students' mathematics literacy abilities were low in terms of level one and two. Level one includes the ability to use knowledge about mathematical concepts directly. Level two includes the ability to use mathematical knowledge procedurally in solving problems. Mathematics literacy abilities are influenced by mastery of mathematical content and mathematical process thinking ability. Most students mistakenly understand the properties and difficult to solve the problem of measuring geometry. Students also find it difficult to draw conclusions due to errors in understanding the purpose of mathematical problems in real life contexts. Based on these findings, learning activities need to be designed optimally so that students can master mathematical concepts in a structured manner.